Freeing the authentic self: phases of recovery and growth from an abusive cult experience - Jenkinson, Gillian (2016)
Abstract This cross disciplinary research study explores former cult members’ perspectives on what helped them to recover from an abusive-cult experience. Here the term ‘abusive-cult’ pre-supposes a psychologically restrictive, traumatic or abusive experience, which may be challenging to ‘recover’ from. As a psychotherapist and former cult member, the subject is of both professional and personal interest.